HUBUNGAN POLA PIKIR, KEPERCAYAAN DIRI DAN DUKUNGAN SOSIAL TERHADAP KECEMASAN AKADEMIK SISWA MA MU’ALLIMIN NWDI PANCOR - Tuzzahrok, Siti Malika; Majdi, Muhammad Zuhdi Zainul; Suhaili, Suhaili (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the relationship between mindset, self-confidence, and social support on students' academic anxiety at MA Mu’allimin NWDI Pancor, with the purpose of understanding the role of each factor in shaping students’ psychological conditions and providing a basis for developing effective learning strategies and interventions. The research employed a quantitative approach with a correlational design, using proportional random sampling from the entire student population. Data were collected through Likert-scale questionnaires measuring mindset, self-confidence, social support, and academic anxiety. Validity was tested using item-total correlation, reliability via Cronbach’s Alpha, and data were analyzed with multiple correlation and multiple linear regression after classical assumption testing. The results indicate that mindset, self-confidence, and social support are negatively and significantly associated with academic anxiety, with self-confidence being the most dominant factor. Simultaneous regression analysis showed that these three variables explained 67.4% of the variability in students’ academic anxiety, highlighting the importance of a holistic approach that combines internal factors with external support to effectively reduce academic anxiety. This study emphasizes the integration of a growth mindset, enhancement of self-confidence, and strengthening of social support as multidimensional intervention strategies in Islamic education.